Toxoplasma gondii: Serological characterization and immunogenicity of recombinant surface antigen 2 (SAG2) expressed in the yeast Pichia pastoris - Lau, Y.L.; Fong, M.Y. (Elsevier, 2008)
The full length surface antigen 2 (SAG2) gene of the protozoan parasite Toxoplasma gondii was cloned and intracellularly expressed in the Pichia pastoris expression system. The molecular weight of the expressed recombinant SAG2 (36 kDa) was much larger than the native SAG2 (22 kDa). This discrepancy in size was due to hyperglycosylation, as deglycosylation assay reduced the size of the recombinant SAG2 to 22 kDa. Despite being hyperglycosylated, the recombinant SAG2 reacted strongly with pooled anti-Toxoplasma human serum, pooled anti-Toxoplasma mouse serum and a SAG2-specific monoclonal antibody. The glycosylated recombinant SAG2 was further evaluated in Western blot and in-house enzyme-linked immunosorbent assay (ELISA) using 80 human serum samples, including confirmed early acute (IgM positive, IgG negative; n = 20), acute (IgM positive, IgG positive; n = 20) and chronic (IgM negative, IgG positive; n = 20) toxoplasmosis patients, and toxoplasmosis negative control patients (n = 20). Results of the Western blot showed that the recombinant SAG2 reacted with all 60 samples of the toxoplasmosis cases but not with the Toxoplasma-negative samples. The sensitivity of in-house ELISA was 80, 95 and 100 for early acute, acute and chronic patients' serum samples, respectively. Vaccination study showed that serum from mice immunised with the glycosylated recombinant SAG2 reacted specifically with the native SAG2 of T. gondii. The mice were significantly protected against lethal challenge with live T. gondii RH strain tachyzoites (P < 0.01) and their survival time was increased compared to controls. Therefore, the present study shows that the A pastoris-derived recombinant SAG2 was specific and suitable for use as antigen for detecting anti-Toxoplasma IgG and IgM antibodies. The vaccination study showed that recombinant SAG2 protein was immunoprotective in mice against lethal challenge. (c) 2008 Elsevier Inc. All rights reserved.